Comparative expression analysis in three Brassicaceae species revealed compensatory changes of the underlying gene regulatory network - Pietsch, Jessica; Deneer, Anna; Fleck, Christian; Hülskamp, Martin (Frontiers in Plant Science, 2023)
Although the gene regulatory network underlying trichome patterning involves more than 15 genes, it is possible to explain patterning with only five components, which raises questions about the relevance of the components and their function in addition to the established core gene subnetwork. Here, we address this question by comparing the relative expression of all patterning genes in three related species. As the involved proteins exhibit differential complex formation, which is assumed to be a conserved regulatory mechanism, we reasoned that those genes belonging to the core network should exhibit similar expression ratios in different species. In this study, we used this as a criterion to assess the relative importance of the patterning genes. We find several striking differences and analyse these in closer detail through a mathematical modelling approach, thus providing predictions on possible mechanisms of adaptation.